Mixed-convection heat transfer from simulated air-cooled electronic devices: experimental and numerical study - Hrairi, Meftah; Ahmed, Mirghani Ishak; Ismail, Ahmad Faris (American Institute of Aeronautics and Astronautics, 2010)
Air-cooling characteristics of an electronic-device heat sink have been experimentally and numerically investigated under various operating conditions for air. Flowing air velocities of 0–7:1 m=s were circulated through a wind tunnel with a rectangular section. The lower surface of the wind tunnel was equipped with 5 by 3 heat sources subjected to uniform heat flux. From the experimental measurements, surface temperature distributions of the discrete heat sources were obtained and effects of Reynolds numbers on these temperatures were investigated. A computational fluid dynamics analysis of the cooling process was conducted to simulate the system and to calculate the required cooling rate. A relation was identified between the thermal-wake function and capability of the software to give better estimations of the circuit-board temperatures. Overall, the obtained results showed good agreement between the simulation and the experimental results. In particular, it was found that surface temperatures of heated modules decrease with increasing Reynolds number.